Development of PBL-Based Student Worksheets to Improve Students' Critical Thinking Skills in Biology Subjects - Novi Indah Lestari; Yuni Ahda; Linda Advinda; Muhyiatul Fadila (Ta'dib, 2025)
The purpose of this research is to develop Biology Student Worksheets (LKPD) based on Problem Based Learning (PBL) to improve students' critical thinking skills on valid, efficient and efficient respiratory and excretory system materials. This type of study is a 4-D form development study consisting of 4 steps, namely define, design, develop, and disseminate. The study points are students of class XI MAN 02 Sijunjung in the 2023-2024 academic year. Validity trial information is obtained through the approval sheet by the lecturer as the validator. Practicality trial information is obtained from the results of the analysis of teacher and student reaction questionnaires. Success trial information is obtained from the multiple-option question sheet to assess students' critical thinking skills. The validation results by the validator on the PBL-based Biology LKPD show a validity value of 84.1% with a very valid category. The practicality results by the Biology teacher show a value of 86.9% with a very practical category, and students 82.81% with a very practical category. The results of the effectiveness test of students' critical thinking skills showed that the PBL-based Biology LKPD was effective, as seen through the critical thinking skills test which showed higher critical thinking skills in the experimental class (83.5%) compared to the control class (74.5%). Thus, it can be concluded that the PBL-based Biology LKPD developed is valid, practical, effective, and can improve students' critical thinking skills.